2023
DOI: 10.1136/bmjopen-2022-069691
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose RaDiation therapy for patients with KNee osteoArthritis (LoRD-KNeA): a protocol for a sham-controlled randomised trial

Abstract: IntroductionLow-dose radiation therapy (LDRT) for osteoarthritis (OA) has been performed for several decades. However, supporting evidence from randomised studies using modern methodologies is lacking, and a recently published randomised study failed to show the significant benefit of LDRT. The presented trial aims to evaluate the efficacy and safety of LDRT for patients with knee OA.Methods and analysisThis prospective, multicentre, randomised trial will be conducted in the Republic of Korea. A total of 114 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…As for the twice weekly regimen rather than a daily RT, it was related to the LDRT as a treatment for osteoarthritis (OA). Several studies have demonstrated the efficacy of LDRT in modulating immune function, and it is used in European countries to relieve the symptoms of uncontrollable OA [26][27][28]. The most common regimen is to perform LDRT two to three times a week [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the twice weekly regimen rather than a daily RT, it was related to the LDRT as a treatment for osteoarthritis (OA). Several studies have demonstrated the efficacy of LDRT in modulating immune function, and it is used in European countries to relieve the symptoms of uncontrollable OA [26][27][28]. The most common regimen is to perform LDRT two to three times a week [28].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the efficacy of LDRT in modulating immune function, and it is used in European countries to relieve the symptoms of uncontrollable OA [26][27][28]. The most common regimen is to perform LDRT two to three times a week [28]. The interfraction interval is based on research by Moon et al [29].…”
Section: Discussionmentioning
confidence: 99%
“…positron emission tomography (PET) plays a crucial role in assessing metabolic activity in tissues, where accurate attenuation correction is imperative to derive precise and quantifiable metabolic information [7][8][9]. Furthermore, when it comes to therapy, radiation therapy planning requires the precise delivery of radiation to target tissue while minimizing exposure to surrounding healthy structures, where the level of accuracy in targeting is critical to the effectiveness and safety of the treatment [10,11]. Conventionally, CT scans are fundamental for both attenuation correction and radiation therapy planning, serving as the primary modality for generating patient-specific attenuation maps.…”
Section: Introductionmentioning
confidence: 99%